A Method of UWB Radar Vital Detection Based on P Time Extraction of Strong Vital Signs. (20th September 2021) - Yang, Zhen; Cheng, Jiming; Qi, Qingjie; Li, Xin; Wang, Yuning
Abstract : The vital sign information in the echo signal of the UWB radar is weak, because of the interference of complex noise. In this paper, a method named P times extraction of strong vital signs for processing echo signals of UWB radars is proposed. Different noises can be distinguished by the cumulative probability distribution of the echo signal and using different methods for processing according to corresponding characteristics. The vital sign information which most clearly represents the trapped person is selected using P times extraction of strong vital signs; then, the respiration and heartbeat rates are extracted. At 5 different distances, multiple sets of tests were carried out on static trapped persons and micromovement trapped persons and using a computer to extract vital signs from the obtained data. Experimental data shows that the algorithm proposed in this paper can extract the respiration and heartbeat rates of trapped persons, with small relative errors and variances, and has a certain reference value for UWB radar signal processing.